analisis pupuk subsidi dan pengaruhnya terhadap produksi jagung di Desa Jono Kecamatan Temayang Kabupaten Bojonegoro - Aisa, Siti Nurul; Nuhfil Hanani; Sujarwo (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
This study aims to analyze the effectiveness of fertilizer subsidies and their impact on maize production in Jono Village. The research utilizes a mixed-method approach, combining quantitative analysis of production data and qualitative examination of subsidy implementation. Quantitative analysis involves assessing maize production trends and the correlation between fertilizer subsidy utilization and yield. Qualitative methods include interviews with farmers and stakeholders to understand perceptions and challenges related to subsidy distribution and usage. The study's findings contribute to a comprehensive understanding of the role of fertilizer subsidies in maize production and provide insights for policymakers and agricultural practitioners. This study employs both quantitative and qualitative descriptive analysis methods to determine the effectiveness of fertilizer subsidies. The research findings indicate that the effectiveness of fertilizer subsidy policy is categorized as ineffective across four indicators: price, quantity, timing, and location. The subsidy has a positive and significant impact on maize production at a significance level of 5%.